2015
DOI: 10.1080/09650792.2014.994016
|View full text |Cite
|
Sign up to set email alerts
|

Improving numeracy outcomes for children through community action research

Abstract: Virtue, according to Aristotle, is doing the right things at the right time with the right people for the right end and in the right way. This concept is central to the work of the Early Learning Initiative, an Irish community-based educational initiative. This paper describes how a community of parents, early childhood care and education practitioners and a third-level institution used action research to develop a three-year numeracy programme for children aged zero to six years. The Early Numeracy Project wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Regarding the second category, students seem to find school activities interesting and pleasant since these can lead to advanced reasoning, intelligence, socialization, and a future career. A similar action research study (Bleach, 2015) indicated students' interest for activities in the classroom through which they feel satisfied and willing to participate in.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding the second category, students seem to find school activities interesting and pleasant since these can lead to advanced reasoning, intelligence, socialization, and a future career. A similar action research study (Bleach, 2015) indicated students' interest for activities in the classroom through which they feel satisfied and willing to participate in.…”
Section: Discussionmentioning
confidence: 92%